Optimization of Poly Aluminum Chloride Liquid Dosage in Clean Water Treatment Using Box-Behnken Design - Purnamasari, Erianti Siska; Patrakomala, Nira; Wahyuni, Sri; Salimi, Sonny (Jurnal Kartika Kimia, 2025)
Various human activities that are increasing will have an impact on the decline in the quality of raw water, a key source of clean water production. To achieve optimal results in the clean water treatment process, a suitable formulation is required for the addition of liquid PAC, which acts as a coagulant to reduce the turbidity level of raw water. Currently, the formulation of liquid PAC dosage in raw water treatment has an accuracy level of less than 70%. Therefore, a method is needed to improve the accuracy level of PAC dosage. Box-Behnken Design (BBD) is one of the RSM design methods, which can analyze problems whose responses are influenced by several variables, where the interaction can be used to predict the optimal formula. This study aims to determine the optimal dosage of liquid PAC required for clean water treatment using the Box-Behnken Design. Before the optimization process is carried out, it is necessary to select parameters that have a significant effect. The methodology in this study is divided into two main stages. The first stage involves parameter selection using Design-Expert Two-Level Factorial, with five parameters tested: liquid PAC dosage, turbidity, pH, stirring speed, and stirring time. The second stage involves optimizing parameters that have a significant effect using Design-Expert Box-Behnken. The results obtained from the parameter selection process indicate that turbidity and liquid PAC dosage have a significant effect. Optimization is carried out by entering the turbidity parameters and liquid PAC dosage as independent variables, with the response being the final turbidity. The results show that in water with turbidities of 20 NTU, 60 NTU, and 100 NTU, the optimum liquid PAC concentration is 50 ppm, with percentage reductions in turbidity of 95.72%, 97.13%, and 97.37%, respectively. BBD shows that there is a significant parameter interaction between the turbidity parameter and the liquid PAC dosage, while there is no significant interaction between the turbidity parameter and pH, and the pH parameter and the liquid PAC dosage.